A systematic literature review on renewable energy technologies for energy sustainability in Nepal: Key challenges and opportunities - Adhikari, Dilli Ram; Techato, Kuaanan; Jariyaboon, Rattana (Center of Biomass & Renewable Energy (CBIORE), 2024)
Energy security is getting louder globally as there are growing concerns about the risk of climate change from using traditional non-renewable energy sources. This systematic literature review is conducted to identify the current state of renewable energy technologies in Nepal supporting the energy sustainability issue, opportunities, and challenges. The peer-reviewed journal articles published in Scopus, Web of Science, and Google Scholar databases were searched with specified search strings. Preferred Reporting Items for Systematic Reviews and Meta-Analysis(PRISMA) framework was utilized to search and screen the relevant literature published from 2012 to 2023 related to renewable energy development in Nepal. The Biblioshiny () function of the R-tool was utilized to conduct the meta-analysis of the identified literature. The result shows that the majority of articles were produced after 2019 and among them 50% of the research were conducted on mixed renewables, 19.4% on hydro, 14.5% solar, 8.1% wind, and 8.1% bio-energy. Renewable energy, climate change, sustainability, and policy interventions were identified as major themes in the research. Biomass (66.4%) still dominates the total energy mix and hydropower dominates in electricity generation. This review has explored how the studies were conducted on energy sustainability and renewable energy technologies in the context of Nepal. The review also provides challenges faced by Nepal’s renewable energy sectoral development and the underlined opportunities towards energy sustainability.